Epidemiological surveillance of the HIV/AIDS complex through the analysis of trends in the incidence of Kaposi’s sarcoma in Cali, Colombia (Colombia Medica, 2012)
Introduction: The Kaposi’s sarcoma (KS) incidence has markedly changed in the general population since the onset of the AIDS epidemic in the eighties and after the introduction of the Highly Active Antiretroviral Therapy (HAART) in the nineties. Objective: To investigate incidence rate trends for Kaposi’s sarcoma before and during the (HIV/AIDS) epidemic in Cali, Colombia. Methods: Exploratory ecological study that included all Kaposi’s sarcoma cases identified by the Cali Cancer Registry from 1962-2007, and 12,887 cases of HIV/AIDS recorded in the Municipal Health Secretariat of Cali between 1986 and 2010. The joinpoint regression model was used to conduct the incidence rate analyses between the years 1962 and 2010. Results: A total of 349 KS cases were identified during the study period. Only 5.3% of the cases (n=20) were diagnosed in the pre-epidemic era (1963-1987), of these, 35.0% were women, and 90.0% of the tumors were located on the skin. In contrast, 94.7% of KS cases (n=329) were discovered after the emergence of HIV-AIDS. There was a significant decrease in the proportion of women (10.9%, p